PENGARUH WELDING REPAIR TERHADAP SIFAT MEKANIK PADA PENGELASAN GTAW BAJA DUPLEX UNS S32760 - Muhamad Nur Juanda; Herry Oktadinata; Taufiqullah - (Jurnal Ilmiah Teknik Mesin, 2019)
Technological developments in the increasingly advanced industrial sector cannot be separated from the welding method, one of which is welding repair. Welding improvements can affect the mechanical properties and microstructure of the material used. This research was conducted to determine the effect of welding repair on UNS S32760 stainless steel duplex material using ER 2594 welding wire which was applied to a vacuum vessel tank. The process of welding original welding in sample 1 using a welding wire with a diameter of 2.4 mm receiving the largest heat input 1.394 kJ / mm. The welding repair process carried out on sample 2 using 2.4 mm diameter welding wire received the largest heat input 1.111 kJ / mm and in sample 3 also experienced welding repair using a welding wire of 2.00 mm receiving the largest heat input 1.347 kJ / mm. The impact test results showed a decrease in the toughness value in sample 2 and sample 3 which underwent welding repair. While the results of Vickers hardness testing increased in sample 2 and sample 3 which underwent a repair welding process, was directly proportional to the increase in heat input received in each sample. The microstructure in samples 2 and 3 changed the phase of Ferrite to Acicular Ferrite. In the HAZ and WL regions in sample 3 Ferrite Grain Boundary is also formed, where Grain Boundary-Ferrite is formed first in the transformation of Austenite to Ferrite, which usually forms along the Austenite boundary. In this research, welding repair process that has mechanical properties close to the mechanical properties of Base Metal is sample 2 which uses 2.4 mm diameter welding wire for welding repair.